Proportion of Japanese primary school children meeting recommendations for 24-h movement guidelines and associations with weight status. Issue 3 (May 2020) - Tanaka, Chiaki; Tremblay, Mark S.; Okuda, Masayuki; Inoue, Shigeru; Tanaka, Shigeho
Abstract: Background: 24-h movement guidelines were recently developed to improve both the present and future health of children. The purpose of the present study was to evaluate adherence to the three recommendations strongly associated with health in 24-h movement guidelines and their relationship with weight status (overweight/obesity or underweight) in Japanese primary school children. Methods: This cross-sectional study was based on 902 children. Weight status according to measured body mass index (BMI) was classified by the WHO growth reference. Meeting the 24-h movement guidelines was defined as: 9–11 h/night of sleep, ≤2 h/day of screen time, and at least 60 min/day of moderate-to-vigorous physical activity (MVPA). Results: The prevalence of children meeting the all three recommendations was 10.5% and 13.2% met none of the three recommendations. Children meeting all three behaviors recommendation, screen time and MVPA or sleep recommendations, or only screen time recommendation had lower odds ratios adjusted for age, gender and socioeconomic status of each school for overweight/obesity compared to children meeting none of the 3 recommendations. Conclusions: The screen time recommendation or combinations including screen time recommendation were associated with overweight/obesity. On the other hand, none of the recommendations was associated with underweight.